Julián Arce Ramírez: a tribute - Neyra Ramírez, José (2009)
Within our sense for living, we have a clear obligation to pay tribute and to continue the pathway set by those who have been the real leaders of Peruvian medicine. Consequently, this is a tribute to Dr. Julian Arce-Ramirez, a very famous and wellrespected Peruvian physician, a distinguished citizen, and a loyal supporter of every noble cause.